ROUGH SESTS-INSPIRED EVOLUTIONARY ALGORITHM FOR ENGINEERING MULTIOBJECTIVE OPTIMIZATION PROBLEMS - hussein, mohamed abdelsameea (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
<!--[if gte mso 9]> A reference point based multi-objective optimization using a combination between trust region (TR) algorithm and particle swarm optimization (PSO) to solve the multi-objective environmental/economic dispatch (EED) problem is presented in this paper. The E IEEE Environmental/Economic Dispatch; Trust Region; Particle Swarm Optimization; Multi-Objective Optimization 14.00 800x600 <![endif]--> <!--[if gte mso 9]> A reference point based multi-objective optimization using a combination between trust region (TR) algorithm and particle swarm optimization (PSO) to solve the multi-objective environmental/economic dispatch (EED) problem is presented in this paper. The E IEEE Environmental/Economic Dispatch; Trust Region; Particle Swarm Optimization; Multi-Objective Optimization 14.00 800x600 <![endif]--> <!--[if gte mso 9]> Print 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> In this paper we present a new optimization algorithm, the proposed algorithm operates in two phases: in the first one, multiobjective version of genetic algorithm is used as search engine in order to generate approximate true Pareto front. This algorithm based on concept of co-evolution and repair algorithm for handling nonlinear constraints. Also it maintains a finite-sized archive of non-dominated solutions which gets iteratively updated in the presence of new solutions based on the concept ofÂ  Îµ -dominance. Then, in the second stage, rough set theory is adopted as local search engine in order to improve the spread of the solutions found so far. The results, provided by the proposed algorithm for engineering optimization problems, are promising when compared with exiting well-known algorithms. Also, our results suggest that our algorithm is better applicable. <!--[if gte mso 9]> Print 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->